The effect of pyruvate supplementation on critical power - Ebersole, K. T.; Housh, T. J.; Evetovich, T. K.; Smith, D. B.; Stout, J. R.; Eckerson, J. M. (The Journal of Strength and Conditioning Research, 2000)
The critical power (CP) cycle ergometer test, theoretically, provides an estimate of a power output that can be maintained without fatigue. It has beensuggested that pyruvate (PYR) supplementation may enhance endurance capacity. Therefore, the purpose of this study was to examine the effect of PYR supplementation on CP. Using a double-blind random design, 9 male and 9 female (mean age ± SD = 20.7 ± 3.5 years) university crew team members were assigned to 1 of 2 treatment conditions: (a) placebo (PL, n = 9) or (b) pyruvate (PYR, n = 9). Prior to supplementation, CP for each subject was determined from 3 workbouts to exhaustion on a cycle ergometer. Each subject was posttested at the same power outputs after ingesting the PL or PYR supplement for 14 consecutive days. The results indicated that PYR supplementation had no (p > 0.05) effect on CP (PL group, pretest CP = 203 ± 45 W, posttest CP = 201 ± 49 W; PYR group, pretest CP = 202 ± 47 W, posttest CP = 207 ± 45 W). These data suggest that 8.1 g·d1 of PYR does not elicit improvements in endurance capability as measured by the CP test.